The Influence of Social Media Marketing on Brand Loyalty Mediated by Brand Trust and Brand Equity at the Grand Family Mother and Child Hospital - Elizabeth Margaretha P, Tantri Yanuar Rahmat Syah, Cri Sajjana Prajna Wekadigunawan (CV. Bunda Ratu, 2023)
Digital technology has changed the way companies do business, including the way companies market their products or services, because the power of digital transformation, especially through social media, can effectively influence consumer purchasing behavior and brand equity. The research was conducted with the aim of finding out the influence of social media marketing on brand trust, brand equity and brand loyalty. Then to find out the influence of brand trust on brand equity, brand equity on brand loyalty, and to find out the influence of the role of mediating variables brand trust and brand equity on the relationship between social media marketing and brand loyalty. This research is included in the type of explanatory causality research, with the research population being all RSIA Grand Family patients who actively use social media. The number of samples in this study was 145 respondents, and the sample method was non-probability sampling. The Structural Equation Model (SEM), together with the Lisrel (Linear Structural Relation) program version 8.80, was used to analyze the data in this study. The results of this research found that social media marketing has a positive and significant effect on brand trust, brand equity and brand loyalty. Furthermore, the results of this research found that brand trust had a positive and significant effect on brand equity, then brand equity had a positive and significant effect on brand loyalty. In this research, brand trust and brand equity were found to mediate the relationship between social media marketing and brand loyalty. However, this research found that brand trust does not have a significant effect on brand loyalty.